Perfil de sensibilidade microbiana, pesquisa de gene mecA de resistência à meticilina e detecção molecular de genes codificadores de enterotoxinas, em espécies de estafilococos coagulase positiva e negativa, isolados de mastites bovinas - Guimarães, Felipe de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Alguns dos agentes patogênicos de mastite bovina são relevantes em relação à qualidade do leite, bem como, para a saúde pública. Foram estudadas dez fazendas localizadas em cinco regiões do estado de São Paulo. Foram examinadas 1.148 vacas, correspondentes a 4.592 glândulas mamárias avaliadas pelos testes de tamis e CMT. Foram colhidas 1.318 amostras de leite, das vacas positivas na triagem para avaliação microbiológica e contagem de células somáticas (CCS). A frequência dos agentes variou de 0,3 a 36,4%. Do total de isolados de Staphylococcus spp (36,4%), 48,7% corresponderam a estafilococos coagulase negativa (SCN), 34,2% S. aureus e 15,9% outros estafilococos coagulase positiva (SCP). Streptococcus spp foram isolados de 23,3% das amostras, dos quais 41,7% Streptococcus. agalactiae, 41,1% Streptococcus dysgalactiae e 17,3% Streptococcus uberis. Corynebacterium spp. foram isolados em 31,8% dos casos de mastite. As amostras de leite das glândulas mamárias infectadas apresentaram CCS significativamente mais elevada que as negativas. Dos 48,7% de SCN foram identificadas 18 espécies: S. warneri, S. epidermidis, S. hyicus, S. xylosus, S. haemolyticus, S. auriculares, S. cohnii subsp cohnii, S. lugdunensis, S. pasteuri, S. saccharolyticus, S. saprophyticus subsp bovis, S. schleiferi subsp scheleiferi, S. simulans, S. saccharolyticus, S. capitis, S. saprophyticus subsp saprophyticus, S. sciuri subsp sciuri e S. chromogenes. As fazendas, II (27,3%) e III (26,7%) apresentaram maior frequência de SCN, enquanto as fazendas I (13,3%) e X (44,4%) revelaram maior prevalência de SCP sendo as diferenças significantes. Foram avaliados por PCR 263 estafilococos para detecção de gene codificadores das enterotoxinas clássicas. Entre os SCN foram detectados: sea (35,5%) seb (7,1%), sec (6,5%), sed (1,8%) e associações destes genes. Em SCP foram detectados: sea (9,5%) seb (4,4%)...

The purpose of this study was to assess the occurrence of mastitis cases in ten Brazilian dairy herds located in five regions in São Paulo state, to characterize the main etiological agents and, to proceed staphylococcal isolates identification to species level, to perform detection by PCR assays of enterotoxin encoded genes aiming the awareness of their potential capability in producing the classical enterotoxins and, mecA a methicilin resistance gene and, evaluated resistance toward antimicrobials. A total of 4,592 mammary glands of 1,148 dairy cows were examined by strip cup and CMT. From these 1,318 milk samples were collected for microbiological exams. It was isolated 263 (19.9%) staphylococci from mastitis cases and they were identified, as being: S.aureus (34.2%), other CPS (15.9%) respectively, S. intermedius (15.2%), S.hyicus(12.9%) and, S. schleiferi subsp coagulans(3.8%), and CNS (48.7%). Among these 128 CNS isolates eighteen species were identified: S. xylosus, S. haemolyticus, S. auriculares; S. cohnii subsp cohnii, S. lugdunensis, S. pasteuri, S. saccharolyticus, S. saprophyticus subsp bovis, S. schleiferi subsp scheleiferi, S. simulans, S. capitis, S. saprophyticus subsp saprophyticus, S. sciuri subsp sciuri and, S. chromogenes. The more frequently isolated species were: S.warneri (31.3%), S. epidermidis (14.8%) and S.hyicus (12.5%). The milk samples from infected mammary glands showed higher CCS than the negatives. PCR assay was used to determine the presence of classical enterotoxin codifying genes (sea, seb, sec and sed). Among CNS the occurrence of enterotoxin classical genes was determined as: 35.1% for sea, 7.1% for seb, 6.5% for sec, 1.8% for sed) 5.3% for both sea and seb, 3.6% for both sea, sec and sed, 1.8% for both sec and sed. Whereas among CPS isolates the occurrence of enterotoxin... (Complete abstract click electronic access below)
Keywords: Estafilococos; Reação em cadeia de polimerase; Bovino de leite; Public health; Encode enterotoxins genes